2008
DOI: 10.1021/ol800908h
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Macrocyclic Peptomers as Mimics of a Quorum Sensing Signal from Staphylococcus aureus

Abstract: We report the design and synthesis of macrocyclic peptide-peptoid hybrids (peptomers) as analogs of autoinducing peptide I (AIP-I) from Staphylococcus aureus. Our solid-phase synthetic route includes efficient microwave-assisted reactions and a tandem macrocyclization-cleavage step, and we demonstrate its compatibility with parallel synthesis through the generation of a focused peptomer library. One of the peptomers was capable of stimulating biofilm formation in S. aureus, a phenotype linked to AIP-I receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 30 publications
1
61
0
1
Order By: Relevance
“…Furthermore, addition of trAIP-II to S. aureus cultures reduced production of ␦-toxin, a known virulence factor (130), indicating a reduction in virulence potential. Separately, 14 macrocyclic peptide-peptoid hybrid molecules lacking thioester linkages were designed as AIP-1 analogues, and one was found to alter S. aureus biofilm formation in vitro, a known AIP-modulated behavior, although the mechanism of action by the molecule was not investigated (223). The most persuasive evidence that AIP analogue inhibitors can be potential antivirulence compounds comes from experiments done in mice.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Furthermore, addition of trAIP-II to S. aureus cultures reduced production of ␦-toxin, a known virulence factor (130), indicating a reduction in virulence potential. Separately, 14 macrocyclic peptide-peptoid hybrid molecules lacking thioester linkages were designed as AIP-1 analogues, and one was found to alter S. aureus biofilm formation in vitro, a known AIP-modulated behavior, although the mechanism of action by the molecule was not investigated (223). The most persuasive evidence that AIP analogue inhibitors can be potential antivirulence compounds comes from experiments done in mice.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…The RNA-III inhibiting peptide (RIP) 10 inhibits phosphorylation of TRAP leading to reduced biofi lm formation, and RIP has been investigated as an anti-biofi lm agent, successfully preventing infections in multiple animal models (Giacometti et al 2003 ). AIP analogues have also been investigated as antibiofi lm agents; the truncated peptide 11 is a potent AgrC QS antagonist (Chan et al 2004 ), while the peptidomimetic 12 promotes biofi lm formation in S. aureus (Fowler et al 2008 ), and the synthetic RIP derivative FS3 13 ( Fig. 6.2 ) enhances the effi cacy of tigecycline in a rat model of staphylococcal vascular graft infection (Simonetti et al 2013 ).…”
Section: Autoinducing Peptides (Aips)mentioning
confidence: 99%
“…This fact could be attributed to changes in surface charges during growth due to modifications in the chemical composition of the cell wall in response to environmental conditions, or to an excretion of acid metabolites that neutralizes the negative charges of glutamic and aspartic acid residues (Shakerifard et al, 2009) decreasing the repulsion of surfactin and exposing the hydrophobic aminoacid moieties therefore increasing the hydrophobic interactions and favoring the adhesion. Fowler, Stacy, and Blackwell (2008) suggested that cyclic lipopeptides could increase the adherence of S. aureus since they are analogous to quorum sensing autoinducers that stimulate the adhesion of Staphylococci on surfaces. The reduction on adhesion of S. aureus after the pre-conditioning with rhamnolipid 1.0% can be related with the strong reduction of hydrophobicity of polystyrene combined with charge repulsion.…”
Section: Effect Of Biosurfactants On Bacterial Adhesionmentioning
confidence: 99%